Correlation between Lipid Profile and Kidney Function in Ambulatory Heart Failure Patient - Sidhi Laksono Purwowiyoto; Hengkie Frankie Lasanudin; Budhi Setianto; Steven Philip Surya; Wincent Candra Diwirya (Universitas Muhammadiyah Yogyakarta, 2021)
Heart failure contributes to a high number of hospitalizations. Currently, the number of outpatients is more dominant than hospitalized heart failure patients. Unfortunately, a study in the outpatient setting is still limited. This study aims to evaluate the correlation between lipid profile and kidney function in ambulatory heart failure patients. This study is a single-center cross-sectional study. Data were collected from August to September 2020. Data were extracted from 62 medical records of heart failure patients with ejection fraction 45%. Exclusion criteria were life-threatening comorbidity and patient with routine hemodialysis. Data were analyzed with Pearson or Spearman correlation test. Most of the heart failure patients in our outpatient clinic are elderly (60 years old) and male (58%). The researchers found positive correlation of total cholesterol (r 0.39; p 0.001) and triglyceride (r 0.59; p 0.001) to serum creatinine. On the other hand, LDL and blood cholesterol ratio negatively correlated with serum creatinine, r - 0.31; p 0.016; and r - 0.46; p 0.001; respectively. All of this analysis was statistically significant. It concluded that lipid profiles were correlated with kidney function in heart failure patients